Răspuns :
Răspuns:
776/33
Explicație pas cu pas:
56 - 34,(7) + 2,(29) = ?
34,(7) = (347 - 34)/9 = 313/9
2,(29) = (229 - 2)/99 = 227/99
________________________
56 - 313/9 + 227/99 = ?
amplificăm fracțiile pentru a le aduce la același numitor comun (99) :
56/1 (amplificare cu 99) = 5544/99
313/9 (amplificare cu 11) = 3443/99
și ne rămâne :
5544/99 - 3443/99 + 227/99 = 2328/99 (simplificam cu 3) = 776/33
Răspuns:
2328/99
Explicație pas cu pas:
ab,(c)=ab intregi si c/9
34,(7)=34 7/9=(9x34+7)/9=313/9
2,(29)= 2 29/99=(99x2+29)/99=227/99
56-313/9+227/99=(56x99-313x11+227)/99=(5544-3443+227)/99=2328/99